CricRNA in head and neck squamous cell carcinoma: biological functions and clinical prospects - Li, Anqi; Dong, Zhen; Zhang, Chunming (Frontiers in Oncology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent malignant tumor globally, shows an unfavorable prognosis and has a five - year survival rate lower than 50%. Circular RNA (circRNA) is defined as a type of non-coding RNA molecule that forms a covalently closed circular structure through back-splicing, characterized by tissue specificity, high stability, and stability in body fluid detection. Recent research has frequently revealed marked alterations in circRNA regulation in HNSCC and participates in tumor malignant behaviors such as cell proliferation and apoptosis, invasion and metastasis, epithelial-mesenchymal transition (EMT), chemoresistance, and immune evasion through mechanisms like “miRNA sponges,” protein scaffolding, translation templates, and epigenetic regulation. This review aims to provide a systematic and up-to-date consolidation of the latest advances in circRNA research for HNSCC, from its biogenesis and multifaceted functions to clinical translation. Our goal is to uncover novel biomarkers and therapeutic targets for the precise diagnosis and management of HNSCC. This review not only aids in elucidating the complex regulatory networks orchestrated by circRNAs in HNSCC but also highlights their immense potential as novel diagnostic and therapeutic agents, thereby paving the way for future research and clinical application.